Noninvasive Assessment of Liver Fibrosis by Magnetic Resonance Elastography in Patients with Rheumatic Disease on Long-Term Methotrexate Treatment - Arindam Nandy Roy; Anjani Kumar Darapureddy; Yarram Ashok Kumar (Indian Journal of Rheumatology)
Background: Long-term methotrexate (MTX) use is associated with hepatic fibrosis in patients with rheumatic diseases. Liver biopsy (invasive conventional diagnostic procedure for hepatic fibrosis) is associated with sampling errors and procedural risks. Magnetic resonance elastography (MRE) is a novel, reliable, and noninvasive imaging technique with excellent diagnostic accuracy for staging hepatic fibrosis and cirrhosis. Till date, studies are scarce on its use in staging MTX-induced liver fibrosis and cirrhosis. The aim of this study is to assess the usefulness of MRE in detecting and quantifying liver fibrosis and to compare these with biochemical parameters in patients with rheumatic diseases on long-term MTX therapy. Methods: Patients with different rheumatic diseases, aged ≥18 years and on MTX treatment for >5 years were included in the study. Their medical records were reviewed, and data regarding demographics, diagnosis, disease duration, MTX dosage and duration were collected. On the day of MRE examination, series of biochemical parameters were conducted in patients. Predefined cutoff MRE values were used for staging liver fibrosis. Results: A total of 48 subjects diagnosed with different rheumatic diseases on long-term MTX were recruited in the study, and majority of them were female (n = 41). The mean age and body mass index of the patients were 53.56 ± 8.36 years and 28.08 ± 4.43, respectively. Around 37.5% (n = 18) of the patients had abnormal aspartate transaminase (AST)-to-platelet count ratio index (APRI) score. The mean MRE value of the study group was 2.83 ± 0.90 kPa. Around 45.83% (n = 22) of the patients had normal liver stiffness values (<2.5) whereas stages F0 (2.5–2.9 kPa), F1 (2.9–3.5 kPa), F2 (3.5–4.0 kPa), F3 (4.0–5.0 kPa), and F4 (>5.0 kPa) were observed in 12.5% (n = 6), 18.75% (n = 9), 10.42% (n = 5), 10.42% (n = 5), and 2.08% (n = 1) of the patients, respectively. MRE values did not correlate with disease duration and cumulative dose of MTX. However, a positive correlation was observed between MRE and liver biochemical parameters (AST: Alanine transaminase [ALT] ratio, ALT, platelet count, APRI, albumin, and mean liver size; P > 0.05). Conclusion: Considering the risk for complications with liver biopsy, MRE provides a reliable, highly accurate, noninvasive assessment of hepatic fibrosis in patients with rheumatic diseases receiving long-term MTX therapy.